(3JMaI GdYQhV aj dWa GdYQhVs - (3eMeO Hf eMeO Hf HGbQ GdMSjfj GdfGFjfj GdSHRhGQj , HgGA GdOjf, J (B1133 (3g` s
(3ChdgG (B:s
(3CeG HYO agPg JMa YQhV JMa GdYQhV MhJ efgG GdhGLH GdeaQhV def MGhd HMQ GdTYQGf s
(3BNQgG (B:s
(3hgh ebOGQ GdhUjI hGddg SHMGfg hJYGdi CYde hUdi Gddg Ydjg SjOfG s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdYQhV hGdbhGais